Tuvan paroemias with a component-religion (against the background of other languages) - Zinovieva, Elena I.; Alyoshin, Alexey S.; Tskhovrebov, Alan S. (The New Research of Tuva, 2024)
The article examines Tuvan paroemias with religious names against the background of other languages, such as Buryat, Ossetian, Russian, Swedish. Similar paroemias are found in various languages, but the number and composition of proverbial units with religious names differ depending on the cultural and religious background of the speakers, as well as the availability of paremiography sources. The religious syncretism of Tengrian-Shamanism and Buddhism in Tuva has influenced the composition of religious names in proverbs. In addition to the lexemes “Burgan”, “Bogda” and “Lama”, “Ham” and “Aza” also function in Tuvan proverbs. However, Buddhism dominates the paremiological corpus under study in terms of quantity. From a structural point of view, syntactic parallelism prevails in the studied Tuvan proverbs. Similarities between the paroemias in Tuvan and other languages analyzed are observed in the use of religious names, such as the names of priests and mythological figures, in their composition. Both lamas and shamans are evaluated negatively in Tuvan folklore. The same situation can be observed when evaluating priests in Ossetian and Swedish parables, and in Russian. Differences are manifested in the total number of paroemias with a religious component in each language, as well as in the number and composition of religious names themselves. They also differ in the predominance of certain syntactic patterns of paroemia, expressed in cultural attitudes and comparisons. For example, in Tuvan and Russian, the god — devil dichotomy is common, while in Buryat parables, the shaman-strongman distinction is more prevalent. In Ossetian parables, there is a prevalence of the priest-devil relationship, and in Swedish, the priest-mullah contrast. Buddhist beliefs are better reflected in Tuvan parables, while shamanistic beliefs predominate in Buryat.